SLR: Miskonsepsi Siswa dalam Memecahkan Masalah pada Materi Bangun Datar - Rizki Ramadhani; Rora Rizky Wandini (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
A flat shape is a geometric part that only has a perimeter and area. There are various shapes of flat shapes, such as triangle, square, long, parallelogram, rhombus, kite, trapezoid, and circle. The aim of this research is to conduct a literary analysis related to the difficulties faced by students in expressing their ideas in the subject. which are given. The analysis method used is called Systematic Literature Review (SLR). Data collection was carried out by documenting and reviewing 7 national index articles; the articles are then broken down into different areas. Based on the research results, there are thirteen articles that discuss the difficulties experienced by students when solving problems related to the topic of building a flat-sided room. Based on the research results, it can be concluded that there are still problems that students often face when trying to solve problems related to the construction of flat-sided spaces. The most common types of errors are formula errors, errors in shape identification, and errors in understanding the concept of plane figures. This is caused by uneven understanding of concepts, inaccurate determination of formulations, and uneven student bias in understanding the results of flat shapes.